BUILDING A HEALTHY INTERNET WITH MIKROTIK - K Tarigan, Adrian; Dingel, Jonathan; Florenta Butar-Butar, Diana; Panjaitan, Hadi (Universitas Efarina, 2019)
The development of the digital world and technology plays an active role in everyday human life and activities. The use of the digital world and technology provides a lot of information so that it can be accessed easily so that it is not uncommon for the use of technology to be used for things that are not good, such as accessing sites that contain negative content. Not everyone knows how to filter sites that contain negative content, so we need a system that can filter sites that contain negative content. This study aims to build a system that can filter sites on the internet so that healthy internet use can be implemented. Sites are filtered using a web proxy proxy. Data collection was carried out using the literature study method, system design, topology design, and filter application. Testing of blocked sites using a browser. The results of this study web proxies can block sites such as URLs, websites, keywords, and the download process of a file. Web proxies cannot block some sites with certain domains. Filtering with a web proxy takes quite a long time because of the many configurations needed.